Differential Expression of , , and Genes in Various Adipose Tissues and Muscle from Yanbian Yellow Cattle and Yan Yellow Cattle - Shuang Ji; Runjun Yang; Chunyan Lu; Zhengyan Qiu; Changguo Yan; Zhihui Zhao (Asian-Australasian Journal of Animal Sciences, 2014)
The objective of this study was to investigate the correlation between cattle breeds and deposit of adipose tissues in different positions and the gene expressions of peroxisome proliferator-activated receptor gamma (PPARγ), fatty acid synthase (FASN), and Acyl-CoA dehydrogenase (ACADM), which are associated with lipid metabolism and are valuable for understanding the physiology in fat depot and meat quality. Yanbian yellow cattle and Yan yellow cattle reared under the same conditions display different fat proportions in the carcass. To understand this difference, the expression of PPARγ, FASN, and ACADM in different adipose tissues and longissimus dorsi muscle (LD) in these two breeds were analyzed using the Real-time quantitative polymerase chain reaction method (qRT-PCR). The result showed that PPARγ gene expression was significantly higher in adipose tissue than in LD in both breeds. PPARγ expression was also higher in abdominal fat, in perirenal fat than in the subcutaneous fat (p<0.05) in Yanbian yellow cattle, and was significantly higher in subcutaneous fat in Yan yellow cattle than that in Yanbian yellow cattle. On the other hand, FASN mRNA expression levels in subcutaneous fat and abdominal fat in Yan yellow cattle were significantly higher than that in Yanbian yellow cattle. Interestingly, ACADM gene shows greater fold changes in LD than in adipose tissues in Yan yellow cattle. Furthermore, the expressions of these three genes in lung, colon, kidney, liver and heart of Yanbian yellow cattle and Yan yellow cattle were also investigated. The results showed that the highest expression levels of PPARγ and FASN genes were detected in the lung in both breeds. The expression of ACADM gene in kidney and liver were higher than that in other organs in Yanbian yellow cattle, the comparison was not statistically significant in Yan yellow cattle.